Analisis Kemampuan Siswa dalam Menafsirkan Grafik Proses Termodinamika di SMA Negeri 5 - Edwi Agusstiawan; I Komang Werdhiana; Muhammad Jarnawi (Universitas Tadulako, 2021)
This study aims to analyze students' ability to interpret thermodynamic process graphs. The instrument used is a thermodynamic graph test question as many as 13 items in the form of reasoned multiple choice. The methodology used is qualitative. This research was conducted at SMA Negeri 5 Model Palu in the odd semester of the 2018/2019 academic year. The subjects of this study were students of class XII IPA 4. Interview respondents were selected based on the results of the analysis of students' answers. The results of the analysis show that the students' abilities are in the very low category with an average percentage of 33.68%. The ability to interpret symbols is 42.01%, connecting observations is 31.77%, finding patterns is 30.21%, and determining the amount is 30.73%. Students' difficulties in interpreting graphs, namely, considering the graph as an object, confusion in interpreting the position of the direction of the arrow in the graph, not knowing the meaning of the symbols of magnitude in the graph, having difficulty interpreting the area under the graph, unable to distinguish graphs, and unable to see the question as a whole.